2012
DOI: 10.5455/msm.2012.24.182-185
|View full text |Cite
|
Sign up to set email alerts
|

Way of Life as Emphasizing Factors in the Progression of Idiophatic Scoliosis in Adolescence Era

Abstract: Introduction:Idiopathic scoliosis is a significant health problem which occurs in 2%–4% school kids in adolescent age. Reasons of occurrence are not quite clear, there are many theories, but probably it is multifactor disease. Among the theories that are mentioned some of them included environmental and behavioral factors.Aim:Research the impact of some environmental and behavioral factor on development and progression of idiopathic scoliosis in school kids.Methodology:Research was conducted on 421 pupil in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In our study, we found that the prevalence and severity of trunk asymmetry is significantly higher in subjects living in urban areas, than in those living in rural areas. This fact was also reported in 2012 [24]. They studied the influence of environmental and behavioral factors on the development and on the progression of idiopathic scoliosis in school-age children.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, we found that the prevalence and severity of trunk asymmetry is significantly higher in subjects living in urban areas, than in those living in rural areas. This fact was also reported in 2012 [24]. They studied the influence of environmental and behavioral factors on the development and on the progression of idiopathic scoliosis in school-age children.…”
Section: Discussionsupporting
confidence: 56%